Terminator genisys. [videorecording (Blu-Ray)] - Taylor, Alan, 1965-; Schwarzenegger, Arnold; Clarke, Jason, 1969-; Simmons, J. K (Paramount, 2021)
When Sergeant Kyle Reese is sent back to 1984 to protect Sarah Connor and safeguard the future, a sudden turn of events creates a fractured timeline.